1990
DOI: 10.1002/1097-0142(19901015)66:8<1755::aid-cncr2820660819>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of Ecto-5′-nucleotidase activity in acute lymphoblastic leukemia

Abstract: Ecto-5'-nucleotidase (5'-N) activity was determined in 191 patients (71 children and 120 adults) with acute leukemia. Elevated values for 5'-N were registered in common acute lymphoblastic leukemia (ALL), but blast cells of T-cell ALL (T-ALL) and common ALL antigen-negative non-T-ALL had low enzyme activity comparable with the values of acute non-lymphocytic leukemia. Dependence of remission duration on 5'-N activity was analyzed in 74 adults with ALL, treated similarly in a prospective multicenter trial. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The expression of adherence molecules on malignant cells has been reported to influence their resistance to drugs (Graham et al, 1993) and their ability to metastasize (Rudy et al, 1993). In addition to an elevated threshold for sensitivity to some cytostatic drugs, ecto-S'NT+ MDR cells may also display different metastatic behavior and thus may contribute to a poorer prognosis of the disease as shown in clinical studies by Gutensohn and Thiel, (1990) and Pieters et al (1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of adherence molecules on malignant cells has been reported to influence their resistance to drugs (Graham et al, 1993) and their ability to metastasize (Rudy et al, 1993). In addition to an elevated threshold for sensitivity to some cytostatic drugs, ecto-S'NT+ MDR cells may also display different metastatic behavior and thus may contribute to a poorer prognosis of the disease as shown in clinical studies by Gutensohn and Thiel, (1990) and Pieters et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have tried to establish a prognostic significance for the expression of ectoJ'NT in malignant cells. Gutensohn and Thiel (1990) found better remission duration for leukemic patients whose cells had low ecto-5'NT activities. Pieters et al (1992) reported similar findings and demonstrated in their study that the level of ecto-5'NT activity of blast cells and their in vitro resistance to 6-thioguanine were not related.…”
mentioning
confidence: 95%
“…CAT and ␤-Galactosidase Assays-Chloramphenicol acetyltransferase activity was measured at 37°C in a reaction medium containing 1 mM dibutyryl CoA (25 g/assay), 10 M D-threo[dichloroacetyl- [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]chloramphenicol (56 mCi/mmol, 0.25 Ci/assay) in 0.25 M Tris, pH 8.0, buffer. The incubation was initiated by the addition of 2-50 l of cell extract in a total volume of 125 l and terminated after 1-6 h with the addition of 300 l of xylenes.…”
Section: Materials-fetalmentioning
confidence: 99%
“…In contrast, elevated activity of ecto-5Ј-NT has been found in breast carcinoma (11), gastric cancer (12), pancreatic cancer (13), chronic myelogenous leukemia (10,14), cutaneous T-cell lymphoma (15), and Walker 256 carcinoma (16). Human renal carcinoma cell lines induced to differentiate by butyric acid have demonstrated both an increase (Cur cell line) and a decrease (Caki cell line) in ecto-5Ј-NT activity (17), demonstrating a complex, and perhaps context-dependent, pattern of ecto-5Ј-NT expression in differentiation and malignant transformation.…”
mentioning
confidence: 92%
See 1 more Smart Citation